2023
DOI: 10.1108/jrme-11-2021-0150
|View full text |Cite
|
Sign up to set email alerts
|

Strategic orientation and its role in linking human capital with the performance of small and medium enterprises in Indonesia

Abstract: Purpose This study aims to investigate the ways that human capital influences the strategic orientation variables entrepreneurial orientation (EO) and market orientation (MO), which ultimately leverage the firm performance of small and medium enterprises (SMEs) in Indonesia. Design/methodology/approach This study used a quantitative method with a total of 274 SMEs in the Regency of Gresik, East Java, Indonesia, as the observable population. Furthermore, the identified samples obtained through the random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…This is consistent with the research conducted by Ahmad et al (2020), which states that there is a positive influence of market orientation on performance. Several other studies have also found similar results, indicating a relationship between market orientation and business performance (Buli, 2017;Iqbal et al, 2023;Kocak et al, 2017;Mamun et al, 2018). However, a study conducted by Dionysus & Arifin (2020) found that market orientation does not affect the performance of MSMEs.…”
Section: Introductionmentioning
confidence: 56%
“…This is consistent with the research conducted by Ahmad et al (2020), which states that there is a positive influence of market orientation on performance. Several other studies have also found similar results, indicating a relationship between market orientation and business performance (Buli, 2017;Iqbal et al, 2023;Kocak et al, 2017;Mamun et al, 2018). However, a study conducted by Dionysus & Arifin (2020) found that market orientation does not affect the performance of MSMEs.…”
Section: Introductionmentioning
confidence: 56%
“…Regression models using heavy-tailed distributions are prevalent. The presumption of uniformly and separately dispersed errors is relaxed in quantile regression, thereby estimating values for various points on a distribution (Iqbal et al, 2023). Stretching the assumption acknowledges the variability in the businesses chosen for this analysis; the influence of inventiveness on company profitability may depend on firm size and growth.…”
Section: Methodsmentioning
confidence: 99%
“…Yadav and Bansal (2020) suggested in their study that the study of entrepreneurial marketing should also be developed in developing countries. However, existing studies still focus on MSME (micro small and medium) actors (Becherer et al, 2012;Jones et al, 2013;Abdullah et al, 2015;Kowalik et al, 2022;Sun & Lee, 2022;Alqahtani et al, 2022;Deku et al, 2023;Iqbal et al, 2023;Zahara et al, 2023) (Sari et al, 2023). No study has been found from an Islamic perspective.…”
Section: A Introductionmentioning
confidence: 99%